ナンキョク ニ オケル ウチュウ ブッシツ ニ カンスル ケンキュウ 2 ショウワキチ ニ オケル ウチュウジン コウカリョウ ノ ヘンドウ ト イド コウカ ニ ツイテ - 島, 誠; シマ, マコト; 矢吹, 英雄; ヤブキ, ヒデオ; 岡田, 昭彦; アカダ, アキヒコ; SHIMA, Makoto; YABUKI, Hideo; OKADA, Akihiko (国立極地研究所, 1969)
P(論文) Measurements of cosmic dust as a function of the seasonal variation were carried out by the air filtration method at Syowa Station (from January to October, 1967). Physical propertiess (size, fall rate), chemical compositions (Fe, Ni, Si, etc.) and the mineralogical composition of part of the collected spherules were also examined. The accretion rates for cosmic dust were measured at various latitudes (30°N-67°S) by the expedition ship FUJI. From the preliminary result it is concluded that the seasonal variation and the variation with latitude of cosmic dust are not appreciable. departmental bulletin paper